Community participation in solid waste management in Kigoma Urban: A case study of Kigoma Ujiji Municipality - Luvakule, Deogratius Gaston (Mzumbe Univesity, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirement for the Award of Masters of Science in Environmental Management (MSc EM) of Mzumbe University